RESTORATIVE JUSTICE DALAM HUKUM PIDANA ADAT - , Anti Mayastuti (PARENTAL, 2014)
Abstract The concept of restorative justice is one type of alternative sentencing in the criminal justice system in line with the purpose of criminal sanctions in accordance with the concept of customary law, restore the cosmic balance, a balance between the world born with the spirit world, to bring peace between fellow citizens or between community members and the community. Punishment must be fair, that is perceived as fair punishment either by the prisoner or by the victim and the community, thus disturbances, imbalances or the conflict will be lost. Alternative Punishment Theory of Restorative Justice is in accordance with the traditions, customs and culture of Indonesian society that has long developed and practiced in Indonesia through the representation of Indigenous Peoples lives in Indonesia, which is still showing its existence in the reality of the lives of the people of Indonesia through the great value "deliberation to reach an agreement". Keywords: restorative justice, indigenous people, deliberation to reach an agreement